2005
DOI: 10.1159/000083165
|View full text |Cite
|
Sign up to set email alerts
|

Postmyocardial Infarction Mortality in Relation to Depression: A Systematic Critical Review

Abstract: The aim of this review was to survey the literature on depression in patients with myocardial infarction to assess the methodological quality and to test whether depression leads to an increased postmyocardial infarction mortality. Medline, Psycinfo, and www.UMI.com were searched, and researchers were contacted in the autumn of 2003. Thirty-one articles were reviewed. Only seven articles scored above a predefined level of 75% for acceptable quality. The articles lack description of non-responders, recall perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
2
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 42 publications
1
71
2
7
Order By: Relevance
“…An increasing body of literature has demonstrated a relationship between depressive symptoms and the likelihood of subsequent adverse cardiac events (32), although negative findings have been reported (33)(34)(35). It is interesting to note that in our study one increased distress subgroup without elevated scores on depressed affect, but characterized by the absence of positive affect and presence of anxious apprehension and emotional exhaustion, was associated with psychiatric comorbidity and decreased health status.…”
Section: Discussioncontrasting
confidence: 40%
“…An increasing body of literature has demonstrated a relationship between depressive symptoms and the likelihood of subsequent adverse cardiac events (32), although negative findings have been reported (33)(34)(35). It is interesting to note that in our study one increased distress subgroup without elevated scores on depressed affect, but characterized by the absence of positive affect and presence of anxious apprehension and emotional exhaustion, was associated with psychiatric comorbidity and decreased health status.…”
Section: Discussioncontrasting
confidence: 40%
“…The Somatic and Cognitive factors each accounted for 9% of total explained variance, within the ranges of 6-11 % (Somatic) and 8-14% (Cognitive) reported by Ward. The finding that 9% of explained variance in BDI scores was accounted for by somatic factors unrelated to depression indicates that, as suggested by several authors [3,7,[10][11][12], measurement of depressive symptoms with the BDI does pick up some variance related to somatic experience, but not depression. The amount of potential bias due to somatic symptoms, however, was small, and measurement bias did not explain the relationship between depressive symptoms and mortality.…”
Section: Discussionmentioning
confidence: 76%
“…Several recent systematic reviews or meta-analyses of the independent association between post-AMI depression and mortality have concluded that unambiguous conclusions could not be reached because of incomplete control for confounding [7][8][9]. The authors of one of the reviews [7] and others [3,[10][11][12] have argued that existing studies linking depression to cardiac and all-cause mortality post-AMI have not adequately controlled for confounding in measurement of depressive symptoms related to overlap between somatic symptoms ofdepression and cardiac symptoms. Indeed, symptoms characteristically associated with depression, such as fatigue, anhedonia, changes in sleep patterns, changes in appetite, or poor concentration, for instance, could occur as a normal reaction to the AMI, from side effects of its treatment, or from the hospitalization itself [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…it is not depressive disorder per se [28]. Indeed, one recent systematic review showed inconclusive results due to methodological issues [29]. Further research reviewed 10 studies reporting at least 30 fatal events, and showed that in 8 out of 10 of these studies there was no statistically significant relationship between depression and mortality after adjustment for potential confounders [30].…”
Section: Discussionmentioning
confidence: 99%